INVESTIGATION OF THE STEEL AND ALLOYS REFINEMENT FOR SPECIAL CASTINGS - S. I. Pereborshchikov (Литьë и металлургия)
There is shown, that it's possible to deoxidize steel for special castings under the scheme silicon-manganese-aluminium-cerium in the furnaces of small capacity.